Evaluation of Corneal Biomechanical Properties Modification after Small Incision Lenticule Extraction Using Scheimpflug-Based Noncontact Tonometer. (28th August 2014) - Mastropasqua, Leonardo; Calienno, Roberta; Lanzini, Manuela; Colasante, Martina; Mastropasqua, Alessandra; Mattei, Peter A.; Nubile, Mario
Abstract : Purpose. To quantify the effect of small incision lenticule extraction (SMILE) on the corneal biomechanics using Scheimpflug noncontact tonometer (Corvis ST). Methods. Twenty eyes of twenty patients, evaluated as eligible for surgery, with high myopia and/or moderate myopic astigmatism, underwent small incision lenticule extraction (SMILE). All patients underwent Corvis ST preoperatively and postoperatively after 1 week, and 1 and 3 months to observe alterations of corneal biomechanical properties. The main outcome measures were Deformation Amplitude, 1st-AT, and 2nd-AT. The relationship between the amount of stroma removed and the percentage variation of the measured parameters from baseline was evaluated with generalized linear model from each time point. For completeness also intraocular pressure (IOP), central corneal thickness (CCT), and their variations after surgery were evaluated. Results. The ratio between the amount of removed refractive error and, respectively, changes of Deformation Amplitude, 1st-AT, and 2nd-AT were significantly modified at the 1st week after surgery ( P = 0.005 ; P = 0.001 ; P = 0.024 ) . At 1 and 3 months these values did not show statistically significant alterations. Intraocular pressure and central corneal thickness showed statistically significant changes during follow-up. Conclusions. No significant modifications in biomechanical properties were observed after SMILE so this procedure could induce only minimal transient alterations of corneal biomechanics.